2002
DOI: 10.1021/cm011567x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solvent and Secondary Doping in Polyaniline Films Doped with Chiral Camphorsulfonic Acid:  Preparation of a Chiral Metal

Abstract: We present the first study of chirality from the UV to the IR region for a conducting polymer, thereby probing the motion of the metallic "free carriers." Through study of chiral and achiral camphorsulfonic acid (CSA) doped polyaniline (PAN) films cast from different solvents (m-cresol and chloroform) and correlations with secondary doping experiments, we demonstrate that the chirality lies in the order "metallic" regions of the polymer films. Samples were studied by absorption, UV-vis-IR circular dichroism, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 76 publications
(68 reference statements)
1
48
0
Order By: Relevance
“…This UV-vis spectrum is similar to that of doped PANI prepared chemically in aqueous solution. [23] In contrast to the PANI films prepared without oligomers, UV-vis spectra of PANI films prepared in the presence of oligomers have a peak around 420 nm, and a long tail extending beyond 1000 nm in the near-IR region. This so-called ªfree-carrier tailº has been identified previously as a delocalized polaron, which serves as an indicator of an extended PANI conformation.…”
Section: Resultsmentioning
confidence: 97%
“…This UV-vis spectrum is similar to that of doped PANI prepared chemically in aqueous solution. [23] In contrast to the PANI films prepared without oligomers, UV-vis spectra of PANI films prepared in the presence of oligomers have a peak around 420 nm, and a long tail extending beyond 1000 nm in the near-IR region. This so-called ªfree-carrier tailº has been identified previously as a delocalized polaron, which serves as an indicator of an extended PANI conformation.…”
Section: Resultsmentioning
confidence: 97%
“…[ 9 ] Therefore, achieving high conductivity requires chemical control of the synthesis and properly choice of the so-called the primary (acids, oxidizing agents) and secondary dopants (solvents). [10][11][12] By optimizing the transparency and the conductivity of thin fi lms of PEDOT:PSS, high-effi ciency, completely ITO-free lightemitting devices and solar cells have been constructed. [ 7 , 13 ] Applications of PANI, however, have generally been limited by its poor solubility (which makes diffi cult its processability as thin fi lms).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that, such a peak could be observed in the case of (S)-(+)-CSA or (R)-(-)-CSA doped polyaniline films with chirality cast from chloroform solution, but could not from m-cresol solution. [10] Separate controlled experiments were carried out for the understanding of the formation mechanism of the chiral composite nanofibers. A polymerization was performed without using the agent CSA, to which sulfuric acid was added for the purpose of maintaining acidic conditions for polymerization.…”
mentioning
confidence: 99%